Efficiency of Fertilization in Sustainable Wheat Production - Pepó, Péter (Acta Agraria Debreceniensis, 2002)
In sustainable (wheat) production plant nutrition supply and fertilization play decisive roles among the agrotechnical elements, because of their direct and indirect effects on other agronomical factors. In long-term experiments, we studied the roles of agroecological, genetic-biological and agrotechnical factors in the nutrient supply, fertilization and its efficiency in wheat production under continental climatic conditions (eastern part of Hungary, Trans-Tisza) on chernozem soil. Our results have proved that there are different (positive and negative) interactions among ecological, biological, and agrotechnical elements of wheat production. These interaction effects could modify the nutrient demand, fertilizer (mainly nitrogen) response of wheat varieties and efficiency of fertilization in wheat production. The optimum N-doses (+PK) of wheat varieties varied from 60 kg ha-1 (+PK) to 120 kg ha-1 (+PK) depending on cropyears, agrotechnical elements and genotypes. The winter wheat varieties could be classified into 4 groups according to their fertilizer demand, natural and fertilizer utilization, fertilizer response and yield capacity. Appropriate fertilization (mainly N) of wheat could affect both the quantity and quality of the yield. By using optimum N (+PK) fertilizer doses, we could manifest genetically- coded baking quality traits of winter wheat varieties and reduce quality fluctuation caused by ecological and other management factors. The efficiency of fertilization on different baking quality parameters (wet-gluten, valorigraph index etc) were variety specific (the changes depended on genotypes). Our long-term experiments proved that appropriate fertilization provides optimum yield, good yield stability and excellent yield quality in sustainable wheat production. We could this get better agronomic and economic fertilization efficiency with less harmful environmental effects.